On Some Questions of \(wN-\) Spaces - Ge, Xun (Scientia Series A: Mathematical Sciences, 2025)
In this paper, we show that a quotient space obtained from the butterfly space is a separable, MCP-space and is not a \(wN-\) Spaces, which answers a question on \(wN-\) Spaces negatively. We also prove that a locally countably compact space X is an MCP-space if and only if it is a \( k_cβ\text{-space}\), which give a partial answer for a question on MCP-spaces.
Keywords: MCP-Space; \(wN-\) Spaces; \(; k_cβ\text{-space}; \)